2020
DOI: 10.1093/cid/ciaa876
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein, Procalcitonin, and White Blood Count to Rule Out Neonatal Early-onset Sepsis Within 36 Hours: A Secondary Analysis of the Neonatal Procalcitonin Intervention Study

Abstract: Background Neonatal early-onset sepsis (EOS) is one of the main causes of global neonatal mortality and morbidity, and initiation of early antibiotic treatment is key. However, antibiotics may be harmful. Methods We performed a secondary analysis of results from the Neonatal Procalcitonin Intervention Study, a prospective, multicenter, randomized, controlled intervention study. The primary outcome was the diagnostic accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 27 publications
3
53
1
3
Order By: Relevance
“…Therefore, both the start and the length of antibiotic treatment to prevent EOS should not be guided only by CRP measurements [ 3 ]. Furthermore, Stocker et al demonstrated that the negative predictive value of CRP does not increase from 36 h onward [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, both the start and the length of antibiotic treatment to prevent EOS should not be guided only by CRP measurements [ 3 ]. Furthermore, Stocker et al demonstrated that the negative predictive value of CRP does not increase from 36 h onward [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, C-reactive protein (CRP) and procalcitonin (PCT) are the most widely used markers to guide antibiotic therapy, although their early increase after birth is not always related to the onset of infections [ 3 , 4 ]. Recent studies have shown that in cases of suspected EOS, when the neonate has no uncertain symptoms and the blood culture is negative at 36–48 h, the discontinuation of empiric antibiotics, guided by the negativity or reduction of the biomarkers of infection (CRP, PCT, and/or PSEP) is a safe practice and saves improperly used antibiotics and costs, with a low rate of suspected re-infections (less than 1%) but no culture-proven bacterial re-infections [ 5 ], and above all, without study-related mortality [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that CRP is a determining predictor and risk factor for sepsis in adults and newborns. [7][8][9] Albumin (ALB) is another protein produced by the liver, which makes up 40% to 60% of the total proteins in the blood. 10 Serum albumin concentration is frequently used as an indicator of malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Automatic stop orders enforce proactive decisions on continuation, which may induce more personalized decision-making, and can be highly effective in reducing unnecessary continuation of antibiotic treatment ( 137 , 138 ). Such personalized decisions may be further improved if guided by combining risk stratification and age-dependent reference values for biomarkers such as procalcitonin (PCT) and or CRP ( 139 141 ). Serial low CRP values, normal PCT values, or the combination of CRP and PCT can support discontinuation of antibiotics ( 142 ).…”
Section: Treatment Durationmentioning
confidence: 99%